Instability Analysis and Reinforcement Support Technology of Coal-Rock Interbed Roadway in Gaojiazhuang Coal Mine. (30th March 2021) - Liu, Chaolin; Zhang, Guohua
Abstract : In order to effectively solve a series of problems such as the difficulty of coal and rock interbed roadway support in Gaojiazhuang Coal Mine and get a scientific and reasonable optimization scheme of surrounding rock support, theoretical analysis, numerical simulation, ultrasonic detection, field-effect test, and other means are adopted to analyze the instability of coal and rock interbed roadway. The results show that the interbedded roadway has weak interbedded cementation, and its ore pressure is more intense due to the influence of its interbedded weak structural plane. Based on Mohr's strength envelope principle, it is proposed that horizontal stress is the main factor that causes a wide range of shear displacement, penetration crack, and surrounding rock failure of the roof of this kind of roadway. Through the finite element numerical simulation analysis, the deformation and failure law, stress distribution characteristics, and failure area distribution characteristics of coal and rock interbedding roadway surrounding rock are theoretically revealed, and the control effect of different support schemes on roadway surrounding rock deformation is greatly different. Based on the ultrasonic detection technology, it is proved that the roadway side failure has strong zoning characteristics, and the failure range and stress distribution range of the surrounding rock of the belt roadway in the 2103 working face of Gaojiazhuang Coal Mine are detected. Finally, the coupling strengthening support scheme combining prestressed anchor cable and bolt is proposed. The engineering application and the observation of surrounding rock deformation show that the reinforced support technology can effectively enhance the stability of the surrounding rock of the interbed roadway in Gaojiazhuang Coal Mine, and it has a good reference for the surrounding rock conditions of this kind of roadway.